2015
DOI: 10.1016/j.tree.2015.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid zones: windows on climate change

Abstract: Defining the impacts of anthropogenic climate change on biodiversity and species distributions is currently a high priority. Niche models focus primarily on predicted changes in abiotic factors; however, species interactions and adaptive evolution will impact the ability of species to persist in the face of changing climate. Our review focuses on the use of hybrid zones to monitor species' responses to contemporary climate change. Monitoring hybrid zones provides insight into how range boundaries shift in resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
222
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(225 citation statements)
references
References 103 publications
1
222
0
2
Order By: Relevance
“…Changes in temperature and precipitation patterns may shift optimal climates for different forest species. Hence, areas that are now climatically suitable for a given species may cease to be or, on the contrary, climate may determine the enlargement of the potential distribution area of that species (Alfaro et al 2014;Lindner et al 2010;Taylor et al 2015). We found that Eurosiberian conifer and broadleaved trees, which require colder and wetter conditions, will not thrive under the projected future climates, similarly to Ruiz-Labourdette et al (2012) for central Spain Mountains.…”
Section: Discussionmentioning
confidence: 71%
“…Changes in temperature and precipitation patterns may shift optimal climates for different forest species. Hence, areas that are now climatically suitable for a given species may cease to be or, on the contrary, climate may determine the enlargement of the potential distribution area of that species (Alfaro et al 2014;Lindner et al 2010;Taylor et al 2015). We found that Eurosiberian conifer and broadleaved trees, which require colder and wetter conditions, will not thrive under the projected future climates, similarly to Ruiz-Labourdette et al (2012) for central Spain Mountains.…”
Section: Discussionmentioning
confidence: 71%
“…Indeed, moving hybrid zones may represent sensitive indicators for anthropogenic climate change (Taylor et al. 2015). Further, the effects of climate change on hybridizing taxa will have widespread evolutionary consequences.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, the spatio-temporal dynamics of a range expansion can provide evidence of whether hybridization contributes to range expansion (sensu [53,80]). Specifically, if a range expansion can be observed directly by comparing contemporary populations to historical populations (e.g.…”
Section: Testing the Hypothesis That Hybridization Facilitates Speciementioning
confidence: 99%